Harnessing the Power of Leptin: The Biochemical Link Connecting Obesity, Diabetes, and Cognitive Decline - Grasso, Patricia (Frontiers in Aging Neuroscience, 2022)
In this review, the current understanding of leptin’s role in energy balance, glycemic regulation, and cognitive function is examined, and its involvement in maintaining the homeostatic “harmony” of these physiologies is explored. The effects of exercise on circulating leptin levels are summarized, and the results of clinical application of leptin to metabolic disease and neurologic dysfunction are reviewed. Finally, pre-clinical evidence is presented which suggests that synthetic peptide leptin mimetics may be useful in resolving not only the leptin resistance associated with common obesity and other elements of metabolic syndrome, but also the peripheral insulin resistance characterizing type 2 diabetes mellitus, and the central insulin resistance associated with certain neurologic deficits in humans.